2022
DOI: 10.14701/ahbps.22-019
|View full text |Cite
|
Sign up to set email alerts
|

Initial United Kingdom experience of endoscopic ultrasound-directed transgastric endoscopic retrograde cholangiopancreatography

Abstract: Backgrounds/Aims: Gallstone disease is a recognized complication of bariatric surgery. Subsequent management of choledocholithiasis may be challenging due to altered anatomy which may include Roux-en-Y gastric bypass (RYGB). We conducted a retrospective service evaluation study to assess the safety and efficacy of endoscopic ultrasound-directed transgastric endoscopic retrograde cholangiopancreatography (EDGE) in patients with RYGB anatomy. Methods: All the patients who underwent EDGE for endoscopic retrograde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The technical success rate was reported for 13 studies 3,5,16–23,25–27 . No heterogeneity was detected among these studies ( P =0.999, I 2 =0%).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The technical success rate was reported for 13 studies 3,5,16–23,25–27 . No heterogeneity was detected among these studies ( P =0.999, I 2 =0%).…”
Section: Resultsmentioning
confidence: 97%
“…Quality was evaluated as high in 9 studies 3,16,17,19–24 . Details on quality assessment of the included studies are shown in Supplementary Table 1, Supplemental Digital Content 1, http://links.lww.com/JCG/A963.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations